Peter Pan - Barrie; J.M. (London Dreamland publication, 2011)
The story follows Peter Pan, a magical boy who never grows up and lives in the enchanting land of Neverland. Peter, along with his fairy companion Tinker Bell, brings Wendy Darling and her brothers, John and Michael, on a fantastical adventure. Together, they encounter the Lost Boys, face off against the villainous Captain Hook, and experience the wonders of Neverland. The book emphasizes themes of imagination, adventure, and the joy of eternal youth, making it a captivating read for children.